Outcome of transcutaneous edge-to-edge mitral valve repair in patients with diabetes mellitus: results from a real-world cohort. (3rd October 2022) - Kirschfink, A; Alachkar, M N; Vogt, F; Schroeder, J; Lehrke, M; Frick, M; Almalla, M; Marx, N; Altiok, E
Abstract: Background: Transcutaneous edge-to-edge repair (TEER) has become a treatment option for selected patients with severe mitral regurgitation (MR). Analysis of the COAPT trial indicated patients with diabetes mellitus to have higher death rates and a trend to higher rates of heart failure hospitalization (HFH) than those without diabetes. However, in that study only patients with secondary MR with specific criteria were included and there are only limited data on diabetes patients in real-world settings. Purpose: This study sought to evaluate safety and efficacy of TEER in patients with diabetes mellitus in comparison to non-diabetics. Methods: In this monocentric study 340 consecutive patients with severe primary and secondary MR who underwent TEER were included. Immediate results of the procedure, intrahospital as well as one-year outcome were compared between patients with and without diabetes. Results: Diabetes was present in 109 patients (32%) of the study group. Patients with diabetes were younger (75±8 vs. 78±8 years; p=0.003), had more often ischemic cardiomyopathy (68% vs. 48%, p<0.001), previous coronary-artery bypass graft (35% vs. 20%; p=0.002) and arterial hypertension (89% vs. 75%; p<0.001) compared to those without diabetes. All other baseline clinical and imaging characteristics including NYHA class, left ventricular dimensions and function (ejection fraction: 38±13% vs. 41±14%; p=0.10) as well as severity of MR were not different between both patient groups (Table 1). Success of the procedure was comparable between patients with and without diabetes (95% vs. 95%; p=0.84). There was no difference in intrahospital mortality between both groups (5.5% vs. 4.8%; p=0.98). At one-year follow up, there was no difference regarding all-cause mortality (24.2% vs. 23.0%; p=0.72), HFH (37.4% vs. 31.0%, p=0.23), NYHA class (p=0.11) or MR severity (p=0.20) between both groups (Table 2). Conclusion: In contrast to previous published data on patients with diabetes and severe MR TEER seems to be similar safe and effective in a real-world setting compared to non-diabetics. Funding Acknowledgement: Type of funding sources: None.